Central fatness among secondary school adolescents in Ibadan, Nigeria. (2016)
One of the most pressing health problems facing public health in the world today is the astronomically increasing over weight and obesity cases among children and adolescents and Nigeria is not an exception to this problem. The increase in weight and obesity in reality cannot be separated from socio-cultural issues, simply because it cuts across all gender and classes. This study therefore, examined the context (reality in line with existing medical, social and cultural values) of central fatness among secondary school adolescents in Ibadan, Nigeria. The data for the study was collected through structured questionnaires and an assessment of anthropometric measurement. The study reveal increasing over weight and obesity cases among secondary students in, Ibadan, and social construction acceptance of obesity as a symbol of good living plays a major role in the prevalence. Hence, it is as a matter of urgency that there should be a strong awareness on the dangers associated with increasing accumulation of excess fat among secondary adolescents in Ibadan.